Cognitive-Communication Predictors of Employment Outcomes 1 and 5 Years Posttraumatic Brain Injury. Issue 3 (May 2021) - O'Neil-Pirozzi, Therese M.; Lequerica, Anthony H.; Chiaravalloti, Nancy D.; Juengst, Shannon B.; Newman, Jody K.
Abstract : Objective: To examine changes in functional memory, problem solving, comprehension, expression, and social communication over the first 2 years posttraumatic brain injury (TBI) and the ability of each to predict return to work (RTW) outcomes at 1 year and 5 years postinjury. Design: Secondary analysis of data from a multicenter longitudinal cohort study. Setting: Acute inpatient rehabilitation facilities and community follow-up. Participants: A total of 3543 individuals between 16 and 60 years of age who were competitively employed at the time of TBI and had completed year 1, year 2, and year 5 postinjury follow-ups. Main Outcome Measures: Year 1 and year 5 RTW status (± competitively employed) at the time of study completion. Results: Greater function across each of the 5 cognitive-communication abilities was associated with RTW success at 1 year and 5 years post-TBI. At discharge, these 5 abilities showed comparable odds of predicting later employment. At year 1 and year 2 follow-ups, independence with problem solving was the most predictive of employment 5 years post-TBI, followed by social interaction, memory, expression, and comprehension. Conclusions: An increased rehabilitation focus on functional memory, problem solving, comprehension, expression, and social interaction post-TBI has the potential to improve RTW outcomes. Abstract : Supplemental Digital Content is Available in the Text.